Utilization of Three-Dimensional Computer-Aided Preoperative Virtual Planning and Manufacturing in Maxillary and Mandibular Reconstruction with a Microvascular Fibula Flap - Kääriäinen, Minna; Kuuskeri, Marika; Gremoutis, Georgios; Kuokkanen, Hannu; Miettinen, Aimo; Laranne, Jussi (Journal of Reconstructive Microsurgery, 2016)
Background The aim of this study was to analyze the effects of computer-aided three-dimensional virtual planning and the use of customized cutting guides in maxillary and mandibular reconstruction with a microvascular fibula flap.Methods Patients (n = 17) undergoing free fibula flap (n = 18) reconstruction of the maxilla (n = 2) or mandible (n = 15) from January 2012 through March 2014 were enrolled in the study. Preoperatively, patients underwent high-resolution computed tomography of the maxillofacial and lower leg regions. Three-dimensional virtual planning of the resection and reconstruction was performed. Customized cutting guides for maxillary/mandibular resections and fibular osteotomies, and prebend plates were manufactured. Demographic data, surgical factors, and perioperative and postoperative results were evaluated.Results Sixteen patients had malignant disease and one had benign disease. Sixteen of the flaps were osteomuscular and two were osteomusculocutaneous. Mean ischemia time was 99 minutes and mean operative time was 542 minutes. The flaps fitted into the defects precisely and no bone grafts were needed. Mean length of the fibula flap was 74 mm and the mean number of segments in the flap was 2.1.Conclusion Three-dimensional computer-aided preoperative virtual planning allowed for precise planning of the tumor resection and size of the fibula flap, the number and placement of the osteotomies needed, and the manufacture of customized cutting guides. Fibular shaping is easier and faster, which may decrease the ischemia time and total operative time. Exact placement of the flap in the defect may facilitate restoration of the anatomic shape and ossification.
Keywords: maxilla; mandible; reconstruction; fibula flap; virtual planning